AB1146 Pharmacological approach of knee osteoarthritis treatment in primary care in spain. (15th June 2017) - Barbero, M Herrero; Gimenez, S; Vergara, J; Viles, E I Lladό; Martinez, H; Roca, G Rodríguez; Sánchez, L; Díaz, JA Muñoz; Frias, JF; Castaño, A; Jiménez, JJ Díaz; Rodríguez, Ά de Cossío; et al.
Abstract : Background: Osteoarthritis (OA) is the most prevalent joint disease and the leading cause of disability from 60 years onwards. In fact, 14, 8% of the Spanish population has OA. Objectives: This study aimed to analyze the indications and average doses prescribed in the treatment of knee osteoarthritis in Primary Care in Spain. Methods: The EMARTRO study was designed as an observational, multicenter, transversal study to compare probability of suffering a comorbidities based on presence of symptomatic knee OA visited by GPs. Sociodemographic, anthropometric, clinical parameters and clinical variables of interest were recorded. The prescribed medications and doses indicated in syntomatic knee OA were analyzed in patients included in the EMARTRO study. Results: A total of 1173 patients were included, of whom 646 had knee OA. Patients with OA had a mean (SD) BMI of 30.9 (5.1), systolic blood pressure 132.8 (14.5) and diastolic blood pressure 77.9 (9.1) mm Hg. They also had a mean of 4.3 (1.9) comorbidities, the most frequent were hypertension 358 (62.2%), dyslipidemia 336 (58.3%), diabetes mellitus II 126 (21.9%), and gastroesophageal reflux 110 (19.1%). As for the symptomatology, the patients presented a mean (SD) pain in Huskisson's VAS of 65.18 (15.27) mm and algofunctional Lequesne score of 11.35 (4.86). Patients were treated with a mean of 2, 2 medications. The 45.5% of osteoarthritic patients were treated as monotherapy, 35.5% were taking 2 medications for osteoarthritis, 15.3% 3 and 3.7% 4 or more medications. It should be noted, taking into account the high levels of pain, that 15% of the patients did not receive any treatment. Regarding prescribed medications for knee OA, 378 (58.2%) patients were treated with paracetamol at a mean daily dose (SD) of 1, 150.5 (1, 815.5) mg; 232 (35.9%) received NSAIDs, with metamizole being the most prescribed at doses 1, 092 (538) mg, ibuprofen at doses 1, 136 (528, 8) mg and naproxen at doses 941, 8 (238, 5) mg. Next, 131 (20.3%) patients were treated with opioids, tramadol being the most frequent at doses 102.7 (49.7) mg; 87 (13.3%) with SYSADOA being chondroitin sulphate the most frequent at doses 758.7 (247.7) mg. Finally, 87 (13.3%) of the patients were treated with COX-2, mainly with etoricoxib at doses of 69.3 (27.1) mg. Conclusions: Although the patients presented many concomitant pathologies, it is frequent to approach osteoarthritis in polytherapy. In addition, despite the high symptomatology, patients are treated primarily with a mild analgesic such as paracetamol at doses lower than those recommended. It is paradoxical the high prescription of NSAIDs in a population with a high prevalence of cardiovascular and gastrointestinal pathologies as well as an increase in the prescription of opioids. Disclosure of Interest: M. Herrero Barbero Employee of: Bioiberica, S. Gimenez: None declared, J. Vergara: None declared, E. Viles I Lladό Employee of: Bioiberica, H. Martinez Employee of: Bioiberica, G. Rodríguez Roca: None declared, L. Sánchez Employee of: Bioiberica, J. A. Díaz Muñoz: None declared, J. F. Frias: None declared, A. Castaño: None declared, J. J. Jiménez Díaz: None declared, Ά. Rodríguez de Cossío: None declared, R. Belenguer: None declared, J. L. Llisterri: None declared, J. Vergés Milano Consultant for: Bioiberica, Employee of: Bioiberica